2021
DOI: 10.3389/fpsyt.2020.612586
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Childhood Maltreatment and Symptoms of Obsessive-Compulsive Disorder: A Meta-Analysis

Abstract: Background: Previous studies have indicated that childhood maltreatment (CM) may potentially influence the clinical symptomatology of obsessive-compulsive disorder (OCD). Here, we aimed to quantify the relationship between CM and obsessive-compulsive symptoms (OCS) and depressive symptoms in OCD through a meta-analysis.Method: We searched PubMed, Embase, Cochrane Library, and PsycARTICLES databases for articles reporting the association between CM and OCD on April 15, 2020. Random-effect models were used to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…Although it was not the focus of the study, we briefly elaborate on the findings in relation to patients with OCD, which in the present study reported being more absent from school and having experienced a major upheaval between their parents more frequently than the other groups, as well as a higher overall exposure to illness‐related events than the control participants. These findings indicate that patients with OCD might have experienced more adverse childhood experiences, which is in line with previous studies (for reviews, see Brander, Pérez‐Vigil, Larsson & Mataix‐Cols, 2016; Ou, Li, Zheng et al ., 2021). Furthermore, a recent meta‐analysis showed that greater experience with adverse childhood events was associated with more severe symptoms of OCD and depression in OCD patients (Ou et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was not the focus of the study, we briefly elaborate on the findings in relation to patients with OCD, which in the present study reported being more absent from school and having experienced a major upheaval between their parents more frequently than the other groups, as well as a higher overall exposure to illness‐related events than the control participants. These findings indicate that patients with OCD might have experienced more adverse childhood experiences, which is in line with previous studies (for reviews, see Brander, Pérez‐Vigil, Larsson & Mataix‐Cols, 2016; Ou, Li, Zheng et al ., 2021). Furthermore, a recent meta‐analysis showed that greater experience with adverse childhood events was associated with more severe symptoms of OCD and depression in OCD patients (Ou et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that patients with OCD might have experienced more adverse childhood experiences, which is in line with previous studies (for reviews, see Brander, Pérez‐Vigil, Larsson & Mataix‐Cols, 2016; Ou, Li, Zheng et al ., 2021). Furthermore, a recent meta‐analysis showed that greater experience with adverse childhood events was associated with more severe symptoms of OCD and depression in OCD patients (Ou et al ., 2021). Also, there is some evidence that negative life experiences coincide with the onset of OCD symptoms, and therefore might play a special role in the development the disorder (Brander et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that people with OCD who experienced high levels of CAM may show more severe symptoms (Gershuny et al, 2008) and have a reduced response to treatment (Dykshoorn, 2014). Regarding subtypes of CAM, a number of studies have highlighted relationships between OCD and early emotional abuse (Mathews et al, 2008; Ou et al, 2021; Hemmings et al, 2013), and between OCD and early emotional or physical neglect (Lochner et al, 2002; Hemmings et al, 2013; Mathews et al, 2008; Brooks et al, 2016). A smaller number of studies have also reported worse OCD outcomes in people who experienced physical or sexual abuse in early life (Gershuny et al, 2008; Ou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding subtypes of CAM, a number of studies have highlighted relationships between OCD and early emotional abuse (Mathews et al, 2008; Ou et al, 2021; Hemmings et al, 2013), and between OCD and early emotional or physical neglect (Lochner et al, 2002; Hemmings et al, 2013; Mathews et al, 2008; Brooks et al, 2016). A smaller number of studies have also reported worse OCD outcomes in people who experienced physical or sexual abuse in early life (Gershuny et al, 2008; Ou et al, 2021). However, a thorough understanding of the relationships between specific types of CAM and OCD symptoms in adulthood remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research investigated the role of traumatic experiences in OCD, reporting inconsistent findings (e.g., Brander et al, 2016;Grabe et al, 2008;Ivarsson et al, 2016;Pinciotti and Orcutt, 2020;Selvi et al, 2012;Visser et al, 2014). More convincing evidence exists concerning the positive association between exposure to traumatic experiences and obsessive-compulsive symptoms (OCSs), such as checking, ordering, or repeating words in head (Destrée et al, 2021;Orsillo et al, 1996;Ou et al, 2021;Raposo-Lima and Morgado, 2020). OCSs may result from different types of trauma exposure, including physical and sexual assault, emotional and physical neglect (Fontenelle et al, 2021), as well as indirect exposure to traumatic events (e.g., learning about events occurring to someone else) (Pinciotti et al, 2021b).…”
mentioning
confidence: 99%